2000
DOI: 10.1074/jbc.m909687199
|View full text |Cite
|
Sign up to set email alerts
|

Altered Sensitivity to Single-strand-specific Reagents Associated with the Genomic Vascular Smooth Muscle α-Actin Promoter during Myofibroblast Differentiation

Abstract: Stimulation of quiescent AKR-2B mouse fibroblasts with transforming growth factor ␤1 results in uniform conversion to a myofibroblast-like phenotype as judged by a rapid accumulation of smooth muscle ␣-actin mRNA and protein. Because transcriptional regulation of the smooth muscle ␣-actin gene in these cells might be mediated by single-stranded DNA-binding proteins, we have examined the sensitivity of genomic DNA to chemical reagents with specificity for unpaired bases in a region of the promoter previously im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 46 publications
2
48
0
Order By: Relevance
“…As shown above, Egr-1 bound to the SPUR element (positioned between Ϫ59 and Ϫ28 base pairs from the transcriptional start site), whereas regulatory Smads2 and -3 interact exclusively with a THR between positions Ϫ170 and Ϫ150 located ϳ100 base pairs upstream from SPUR (Becker et al, 2000;Subramanian et al, 2004). This eliminated the possibility that Egr-1 and Smads might compete for the same or overlapping DNA binding sites in the promoter.…”
Section: Binding Of Egr-1 To the Sm␣a Promoter Has Opposite Effects Omentioning
confidence: 97%
See 1 more Smart Citation
“…As shown above, Egr-1 bound to the SPUR element (positioned between Ϫ59 and Ϫ28 base pairs from the transcriptional start site), whereas regulatory Smads2 and -3 interact exclusively with a THR between positions Ϫ170 and Ϫ150 located ϳ100 base pairs upstream from SPUR (Becker et al, 2000;Subramanian et al, 2004). This eliminated the possibility that Egr-1 and Smads might compete for the same or overlapping DNA binding sites in the promoter.…”
Section: Binding Of Egr-1 To the Sm␣a Promoter Has Opposite Effects Omentioning
confidence: 97%
“…Transforming growth factor (TGF) ␤1) is the principle mediator of myofibroblast differentiation in healing wounds where it accumulates in granulation tissue in activated form during leukocyte infiltration and potently stimulates transcription of the type I␣2 collagen subunit (COL1␣2) and SM␣A genes (Becker et al, 2000;Massague and Wotton, 2000;Cogan et al, 2002;Higashi et al, 2003;Grotendorst et al, 2004;Leask and Abraham, 2004;Subramanian et al, 2004;Zhang et al, 2005). Smad proteins 2 and 3 are activated by TGF␤1 receptor engagement and enter the nucleus in which they directly bind SM␣A and COL1␣2 promoter DNA.…”
Section: Introductionmentioning
confidence: 99%
“…4, C and D). Relative to A7r5 cells, which exhibit a stable adult VSMC phenotype (46), the VSMP4 reporter predictably showed a higher degree of serum and TGF␤1 inducibility in synchronized AKR-2B cells consistent with transition to a myofibroblast-like phenotype (20). In growth factor-stimulated AKR-2B MEFs, exogenous Pur␣ and Pur␤ were equally effective in attenuating VSMP4 induction (Fig.…”
Section: Functional Consequences Of Pur␣ or Pur␤ Knockdown In Fibroblmentioning
confidence: 99%
“…In its double-stranded configuration, the Pur/ Pyr sequence contains a consensus MCAT enhancer motif, which serves as a recognition site for transcription enhancer factor 1 (TEF-1) (18). Importantly, computer modeling of the extended Pur/Pyr tract coupled with ssDNA-selective chemical modification of genomic DNA in cultured fibroblasts indicated that this region has the propensity to assume a partially unpaired configuration in response to transforming growth factor ␤1 (TGF␤1) signaling (20). These findings coupled with results of in vitro DNA binding and cell-based SM␣A promoter mutagenesis studies, led to the development of two alternative models for cryptic MCAT enhancer regulation.…”
mentioning
confidence: 99%
“…In this regard, a recent report showing direct protein-protein binding between TEF-1 and SRF (47), leads one to question whether this interaction is subject to regulation by Pur␣, Pur␤, MSY1, or some combination thereof. Furthermore, in light of the changes in DNA structure surrounding the genomic Pu/Py element that accompanies myofibroblast differentiation (48), analysis of nucleoprotein complex assembly/disassembly on the genomic promoter will likely provide further insight into the mechanism of MCAT enhancer regulation by Pur␣, Pur␤, MSY1 vis à vis the proposed models. …”
Section: Discussionmentioning
confidence: 99%